Gestão da informação e a análise de processos na ouvidoria da Secretaria de Meio Ambiente de Aracaju - Sales Junior, Wellington Oliveira (2020)
The modernization of management processes has become a sine qua non condition for organizational survival. In recent years, the number of tools to reinforce the decision-making process has increased, however, to make more assertive decisions, it is necessary for the organization to provide the basic requirements for an effective information management; therefore, mapping the flow of information and managing the organizational procedural steps are essential conditions for institutional success, in order to anticipate solutions to remedy nonconformities. Such topics can be applied in the most diverse currents, such as in the management of environmental issues. The theme of this work focuses on information management at the Ombudsman's Office of the Environment Secretariat of Aracaju (SEMA) and aims to promote information management at the SEMA's Ombudsman based on process analysis. For that, the following specific objectives were listed: a) to examine the relationship of the ombudsman within the organizational structure of SEMA; b) map the informational flow of the SEMA ombudsman; c) verify the convergence of SEMA's ombudsman with LAI; d) present a process manual to the ombudsman. The methodology used in this work is descriptive in nature, with a qualitative and quantitative approach, in addition the research strategy was a case study in which it aims to unfold phenomena inserted in a given context. There was a documentary analysis based on the management reports of SEMA, bibliographic research in the literature of Information Science and Administration. In order to know the particularities of the object of study, an interview was conducted, through the application of a questionnaire using the Whatsapp application, respecting the rules of social distance due to the pandemic. With the interview, a content analysis was carried out to identify the most relevant perception for the interviewee. In the quantitative approach, the data were treated using MS Excel to perform descriptive statistics. With this study, it is evident that the ombudsman's office needs to make adjustments to meet the recommendations of the Comptroller General of the Union regarding its organizational structure, as the defined flows favor the loss and duplication of registration of manifestations. It was also observed that the type of manifestations that discriminate against environmental crime, the location and the period of the year can serve as an input for decision making, promoting information management in this environment. At the end, the product proposal is the elaboration of the process manual for the SEMA Ombudsman.